Gibberellins in Flowering and Non-flowering Trees of Pinus caribaea - Rawal, S. K.; Agrawal, D. C. (Indian Forester, 1982)
Long shoots-equivalent to and potential female strobili from a 17 year old flowering and 6 year old non-flowering trees of Pinus caribaea Morelet were extracted, isolated and identified for activity of various polar and non-polar GAs. It was found that total GA actIvity in long shoots of flowering tree was 1.5 times higher than the long shoots of non-flowering tree.